Decadal change of spring dust activity in western Iran and its mechanism - Kamal, Alireza; Lin, Zhaohui; Wu, Chenglai (Frontiers in Environmental Science, 2022)
Western Iran is an important dust source region in Middle East, with strong dust activities occurring in springtime. Based on a three-hourly meteorological station data, remarkable decadal change of dust frequency in the spring season has been found in the west and southwest of Iran, with less dust activities during 1992–2005 (hereafter as “P1”) and more frequent dust activities occurring during 2006–2015 (hereafter as “P2”). The decadal change signal in dust activities is closely associated with the corresponding decadal difference in precipitation and atmospheric moisture transportation in the region. Compared with P1 period during 1992–2005, anomalous moisture divergence over the center of Middle East can be found in P2 period during 2006–2015, suggesting less moisture transport to the western Iran from the Arabian Sea, Red Sea, and the Persian Gulf, hence there is relatively less precipitation and dry soil moisture over the main dust source regions in the study region, which is favorable for more frequent dust emissions in P2 period. Meanwhile, westerly anomaly in P2 period can also be found in western Iran and upstream regions, such as Iraq and Syria, which is favorable for more dust transport to western Iran from upstream dust source region in Middle East. Furthermore, negative SST anomalies in central and western North Pacific and positive SST anomalies in the eastern North Pacific can be found in P1 period, which is corresponding to positive phase of Pacific Decadal Oscillation (PDO). Conversely, a negative phase of PDO can be found during P2 period. This suggests that PDO is the key influential factor for the decadal change of spring dust activities in western Iran.